Relationship between angiogenic growth factors and atherosclerosis in renal transplantation recipients: a cross-sectional study - Çoban, Melahat; Durak, Beyza Algul; Karakan, Mine Sebnem (São Paulo Medical Journal, 2025)
BACKGROUND: Accelerated development of atherosclerosis has been observed in renal transplant recipients (RTRs). Angiopoietin-2 (Ang-2) and vascular endothelial growth factor (VEGF) are vascular enzymes that play important roles in vascular development and angiogenesis. OBJECTIVE: This study aimed to investigate the relationship between Ang-2 and VEGF and atherosclerosis in RTRs. DESIGN AND SETTING: This study was conducted at Ankara City Hospital, Turkey. METHODS: This cross-sectional study included 36 (37.5%) female and 60 (62.5%) male RTRs. All findings were compared with those of 70 healthy controls. Ultrasonographic measurements of the carotid artery intima-media thickness (CA-IMT) and renal resistive index (RRI) were used as indicators of atherosclerosis. RESULTS: Log10 Ang-2, log10 VEGF, CA-IMT, and RRI levels were significantly higher in patients than in healthy controls. No significant differences were detected in CA-IMT and RRI between those with log10 Ang-2 ≥ 3.53 pg/mL and those with < 3.53 pg/mL. No significant differences were detected in CA-IMT and RRI between those with log10 VEGF ≥ 1.98 pg/mL and those with < 1.98 pg/mL. No correlation was detected between log10 Ang-2 and log10 VEGF, CA-IMT, or RRI. CONCLUSIONS: Increased serum angiogenic growth factor levels and increased atherosclerosis development were detected in RTRs compared to healthy individuals. No relationship was observed between angiogenic growth factors and atherosclerosis. This may be due to the decreased synthesis and effect of angiogenic growth factor receptors synthesized from atherosclerotic plaques due to atherosclerosis, which improves after renal transplantation.